Comparing the Molluscicidal Action of Metaldehyde, Oxamyl, Potassium Nitrate and a Botanical Insecticide for Managing Limacolaria Spp Infesting Banana Plantations in Cameroon - Limunga, Tientcheu Cheke Bernadette; Monono, Ekwa Yawa; Mathias, Afui Mih; Okolle, Nambangia Justin (International Journal of Sustainable Agricultural Research, 2020)
Snails are an emerging problem in banana production in Cameroon due to the damages caused on the banana fruits. They attack the banana fruits resulting in aesthetically disfigured fruits. This study was carried out to compare the effectiveness of selected agrochemicals in the laboratory and the field for the control of the snails. The agrochemicals compared were Bromorex® (chilli pepper extracts), Potassium Nitrate, Vydate® (Oxamyl), and Limace® (Metaldehyde). Laboratory results showed that snail mortality caused by the different treatments after 7 and 14 days was highest for Limace (37% and 100% respectively). Limace® had the highest mean percentage (86.4%) of snails at the snail zone as compared with the control (6.1%) which was the least. Field results showed that plants treated with Limace® had the lowest mean number of snails counted on the corms and pseudostems during the 12-week period while the Control (2.67snails/plant) had the highest mean value followed by Bromorex®. But the mean number of living snails with plant treated with Potassium Nitrate, Vydate® and Limace® increased from the 10th week albeit less than 1 snail/plant. During the first three weeks plants treated with Limace® and Vydate® the number of dead snails was relatively higher (1.6 snails/plant and 1.08 snails/plant respectively). Of the four treatments assessed, Limace® was most effective in the management of snails followed by Vydate®. Limace® controlled the snails best both in the laboratory and on the field at concentrations of 5 g per container (7x7x13 cm) and 50 g per banana mat respectively.